Dispersal Politics as Internal Bordering: Migration Governance in the Euro-Moroccan Border Regime - El Arabi, Sofia (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2026)
This article examines migration control in Morocco beyond the spectacle of fences and visible border infrastructures, foregrounding the spatial and temporal rationalities that have structured the dispersal of West and Central African migrants since 2015 within the evolving Euro-Moroccan border regime. Drawing on participatory action research conducted between 2017 and 2020 in informal camps and urban margins, it traces the trajectories of 215 individuals forcibly relocated from northern border cities to peripheral and medium-sized cities in central and southern Morocco. The article conceptualizes dispersal as a biopolitical technology of internal bordering and a central modality of migration politics that redistributes control across national territory, contributing to the territorial thickening of the Euro-Moroccan border and producing forms of political and legal invisibility. It further shows how dispersal participates in the racialized production of migrant illegality across differentiated urban spaces. Through an analysis of Tiznit (south) and Taza (northeast), the article demonstrates how dispersal reconfigures urban governance, embeds precarity within local spatial orders, and fragments migratory trajectories into prolonged conditions of marginality and tactical survival. By shifting the analytical lens toward the southern side of the Mediterranean border regime, the article shows how European migration externalization is internalized and territorially reworked through locally situated practices of mobility control, materializing in a fragmented geography of forced mobility that migrants navigate and contest.